Pregnancy greatly affects the steroidal module of the Athlete Biological Passport. Issue 7 (15th February 2018) - Mullen, Jenny; Gadot, Yifat; Eklund, Emma; Andersson, Alexander; J. Schulze, Jenny; Ericsson, Magnus; Lindén Hirschberg, Angelica; Rane, Anders; Ekström, Lena
Abstract: Concentrations of urinary steroids are measured in anti‐doping test programs to detect doping with endogenous steroids. These concentrations are combined into ratios and followed over time in the steroidal module of the Athlete Biological Passport (ABP). The most important ratio in the ABP is the testosterone/epitestosterone (T/E) ratio but this ratio is subject to intra‐individual variations, especially large in women, which complicates interpretation. In addition, there are other factors affecting T/E. Pregnancy, for example, is known to affect the urinary excretion rate of epitestosterone and hence the T/E ratio. However, the extent of this variation and how pregnancy affect other ratios has not been fully evaluated. Here we have studied the urinary steroid profile, including 19‐norandrosterone (19‐NA), in 67 pregnant women and compared to postpartum. Epitestosterone was higher and, consequently, the T/E and 5αAdiol/E ratios were lower in the pregnant women. Androsterone/etiocholanolone (A/Etio) and 5αAdiol/5βAdiol, on the other hand, were higher in the first trimester as compared to postpartum (p<0.0001 and p=0.0396, respectively). There was no difference in A/T during pregnancy or after. 19‐NA was present in 90.5% of the urine samples collected from pregnant women. In this study, we have shown that the steroid profile of the ABP is affected by pregnancy, and hence can cause atypical passport findings. These atypical findings would lead to unnecessary confirmation procedures, if the patterns of pregnancy are not recognized by the ABP management units. Abstract : In this study, the biomarkers of the steroidal module of the Athlete Biological Passport, and 19‐NA, were monitored in 67 pregnant women. We show that a normal pregnancy may affect all ratios in the steroidal module, therefore most likely causing atypical findings in the steroidal passport. The most apparent result being decreased T/E and 5αAdiol/E due to increased levels of E during pregnancy.